Witnessing Public Mourning in Haudenosaunee Youth Theatre. Issue 2 (1st June 2022) - Francis, Margot
Abstract: While the Indigenous youth suicide crisis in Canada is widely acknowledged, there is little scholarly attention given to writers who reflect on this from the perspective of being suicide survivors. In this article, I consider the play, And She Split the Sky in Two, by Aleria McKay, a youth survivor from Six Nations. I explore how her work functions as an anti-colonial text that re-envisions the suicide crisis at Six Nations through mourning the gendered, affective, systemic, and spatial legacies of colonial violence. McKay's characters are learning to tell their own stories to completion, depathologizing experiences of despair and entrapment. This work provides a girl's perspective on the long slow process of staying alive to create a different future.